Exploring Students' Perceptions of Newsela Integrated to Tri Hita Karana for Enhancing Students’ Reading Comprehension - Ni Made Yuniari; I Made Sutajaya; I Wayan Suja (Widya Accarya, 2025)
This study investigated how the Tri Hita Karana philosophy which placed an emphasis on harmony and balance in the relationships between people, the natural world, and the divine coexisted with Newsela, a digital learning platform. The study looked into how students felt about this integration and how it affected their motivation, engagement, and reading comprehension abilities. With 65% of students expressing satisfaction and 100% agreeing that the integration improved their learning engagement, this study, which used a mixed-methods approach, found a positive association between cultural relevance and comprehension. Furthermore, 70% of participants said they felt more confident while confronting complicated literature, and 80% said the reading materials were easier to understand. The results indicated that integrating regional cultural values into instructional materials enhanced students' overall development besides their academic performance. This study promoted an all-encompassing educational strategy that combined technology with conventional values, emphasizing the possibility of creative curriculum that connected with students' cultural identities and improved their educational experiences in general. To further understand the mechanics of this integration in various educational situations, future research directions are suggested.